Synapsin III is a key component of α‐synuclein fibrils in Lewy bodies of PD brains. (23rd February 2018) - Longhena, Francesca; Faustini, Gaia; Varanita, Tatiana; Zaltieri, Michela; Porrini, Vanessa; Tessari, Isabella; Poliani, Pietro Luigi; Missale, Cristina; Borroni, Barbara; Padovani, Alessandro; Bubacco, Luigi; Pizzi, Marina; et al.
Abstract: Lewy bodies (LB) and Lewy neurites (LN), which are primarily composed of α‐synuclein (α‐syn), are neuropathological hallmarks of Parkinson's disease (PD) and dementia with Lewy bodies (DLB). We recently found that the neuronal phosphoprotein synapsin III (syn III) controls dopamine release via cooperation with α‐syn and modulates α‐syn aggregation. Here, we observed that LB and LN, in the substantia nigra of PD patients and hippocampus of one subject with DLB, displayed a marked immunopositivity for syn III. The in situ proximity ligation assay revealed the accumulation of numerous proteinase K‐resistant neuropathological inclusions that contained both α‐syn and syn III in tight association in the brain of affected subjects. Most strikingly, syn III was identified as a component of α‐syn‐positive fibrils in LB‐enriched protein extracts from PD brains. Finally, a positive correlation between syn III and α‐syn levels was detected in the caudate putamen of PD subjects. Collectively, these findings indicate that syn III is a crucial α‐syn interactant and a key component of LB fibrils in the brain of patients affected by PD.